Commentary: A Significant Transition of Mode of Teaching and Studying to meet the Covid-19 challenges in an university in Vietnam - Le Minh, Thi (Tạp chí Khoa học Nghiên cứu Sức khỏe và Phát triển, 2021)
Since the coronavirus outbreak in January, many schools and universities in Vietnam have almost entirely closed for nearly three months as a means of social distancing. The Ministry of Education has requested institutions to shift to online teaching to ensure students are kept up with their study progress while staying at home, and millions of students have been using different digital online learning approaches to satisfy their home-based learning needs. This paper is to comment on the change and challenges of students and lecturers in adapting training strategies response to Covid 19. Although the social distancing lasted only 3 months and there were some concerns regarding the disadvantages of digital and online way of studying, the training strategies in the Universities have changed significantly. Covid -19 also brings an opportunity in rebuild our education system carefully and adaptably in this sensitive world.